Towards a complete resolution of the genetic architecture of disease - Singleton, Andrew B (2010)
Following years of linear gains in the genetic dissection of human disease, we are now in a period of exponential discovery. This is particularly apparent for complex disease. Genome-wide association studies have provided myriad associations between common variability and disease, and shown that common genetic variability is unlikely to explain the entire genetic predisposition to disease. Here, we detail how one can expand on this success and systematically identify genetic risks that lead or predispose to disease using next generation sequencing. Geneticists have had for many years a protocol to identify Mendelian disease. Now we have available a similar set of tools for the identification of rare moderate risk loci and common low risk variants. While undoubtedly major challenges remain, particularly with data handling and the functional classification of variants, we suggest that these will be largely practical and not conceptual.